2020
DOI: 10.1590/1519-6984.203511
|View full text |Cite
|
Sign up to set email alerts
|

First report of inventory and role of macroinvertebrates and fish in Cautín river (38° S, Araucania region Chile)

Abstract: Abstract The Cautin river is located in the 137 years old Araucania region, Chile (38°S), and is characterized by alterations through human interference due agriculture and towns in its surrounding basin, the presence of salmonids, and by its mixed regime, originated from snow melting in summer and rains in winter. The aim of the present study was to make a review of the inventory and ecological role of the benthic inland water macroinvertebrates of the River Cautin, in order to understand their import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
3
9
0
Order By: Relevance
“…This agrees with descriptions of Miserendino et al (2018) for Argentinean Patagonia, where the main changes are observed in the middle riverbed zones due to decreasing substrate size and oxygen concentration, and increasing temperature. The species reported in the present study agree with the results reported by Vega et al (2020), in a species inventory along the whole Cautín River with no sites specified; this differs from the present study in which the species were associated with different sites.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This agrees with descriptions of Miserendino et al (2018) for Argentinean Patagonia, where the main changes are observed in the middle riverbed zones due to decreasing substrate size and oxygen concentration, and increasing temperature. The species reported in the present study agree with the results reported by Vega et al (2020), in a species inventory along the whole Cautín River with no sites specified; this differs from the present study in which the species were associated with different sites.…”
Section: Discussionsupporting
confidence: 83%
“…The distribution data of the benthic macroinvertebrate communities of the Cautín River have been compared with historical data from 1986 (Vega et al, 2020); this report showed the changes in the benthic macroinvertebrate community since a study dating to 34 years before the present, when the benthic communities located in Temuco (Sites 6 and 7) had a similar composition to that currently recorded in high sector sites. This would confirm the altered state of the lower sectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature about the trophic role of macroinvertebrate in inland waters revealed that in those ecosystems there are herbivorous, detritivores, shredders, omnivorous, carnivorous, and feed on vegetal residuals that originated from the surrounding catchment basins (Figueroa, 2000;Oyanedel et al, 2008Oyanedel et al, , 2011Moya et al, 2009;Encina et al, 2017;Vega et al, 2020). According to the literature (Tables 1 and 2), the amphipods feed on dead vegetal matter and macrophytes, whereas the Ephemeroptera, Trichoptera and Plecoptera larval stages are shredders and decapods feed on dead vegetal matter and also predate on freshwater mollusks, finally freshwater mollusks (gastropoda) are herbivores, detritivorous and scrappers.…”
Section: Trophic Interactions Between Macroinvertebrates and Fishmentioning
confidence: 99%
“…In spite of the differences in the number of species reported, the random associations found between species is a result of the presence of many repeated species in the studied sites (Tondoh, 2006;Tiho and Josens, 2007), which is a very frequent phenomenon in the analysis of inland water communities in Chile. The present study is relevant because it is the first to include terrestrial insects, additional to a previous study on aquatic crustaceans (De Los Ríos- , because both groups probably would have potential interactions that would regulate the presence and absence of the species in each habitat (Vega et al, 2020). However, more detailed studies would be necessary to assess trophic interactions and interspecific competition in these coastal ecosystems.…”
Section: Discussionmentioning
confidence: 99%